2005
DOI: 10.1152/ajpgi.00274.2004
|View full text |Cite
|
Sign up to set email alerts
|

Ecabet sodium inhibitsHelicobacter pylorilipopolysaccharide-induced activation of NADPH oxidase 1 or apoptosis of guinea pig gastric mucosal cells

Abstract: . Ecabet sodium inhibits Helicobacter pylori lipopolysaccharide-induced activation of NADPH oxidase 1 or apoptosis of guinea pig gastric mucosal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Taken together, our finding that VvpE induces proinflammatory responses via an ANXA2-dependent mechanism provides information about the important mechanisms of pathogen-induced cell death during V. vulnificus infection. Increasing evidence has suggested that lipid rafts are clustered to form a redox signaling platform through gp91 phox (NOX2) coupling with cytosolic factors that include p47 phox (NCF1), p67 phox (NCF2), and small GTPase Rac1 (45)(46)(47), and that these processes subsequently produce superoxides and other ROS (45). Although in most cell types, mitochondrial ROS are thought to be the largest contributor to intracellular ROS production (48), our result showed that the sequestration of cholesterol by MbCD attenuates intracellular ROS production and Expression of Ki67 (green) in ileum and jejunum was examined by confocal microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our finding that VvpE induces proinflammatory responses via an ANXA2-dependent mechanism provides information about the important mechanisms of pathogen-induced cell death during V. vulnificus infection. Increasing evidence has suggested that lipid rafts are clustered to form a redox signaling platform through gp91 phox (NOX2) coupling with cytosolic factors that include p47 phox (NCF1), p67 phox (NCF2), and small GTPase Rac1 (45)(46)(47), and that these processes subsequently produce superoxides and other ROS (45). Although in most cell types, mitochondrial ROS are thought to be the largest contributor to intracellular ROS production (48), our result showed that the sequestration of cholesterol by MbCD attenuates intracellular ROS production and Expression of Ki67 (green) in ileum and jejunum was examined by confocal microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…However, using the mouse model, only TLR2 and TLR4 have been proven to be related to atherogenesis (26,27), although it is conceivable that the other types of TLRs should be related as well. Nox1 expression-mediated control of TLR has been demonstrated in colon cells, where LPS produced by Helicobacter pylori is TLR4-dependent in inducing Nox1 expression (28). The presently known Nox1-inducing factors are IFN-␥ and 1␣,25-dihydroxyvitamin D 3 from intestinal epithelium (29,30), and angiotensin II, PGF 2 ␣, and platelet-derived growth factor from VSMCs (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of species-specific distribution of Nox1 as well. Rodent stomach expresses Nox1, which has been shown to be upregulated by Helicobacter pylori lipopolysaccharide (LPS) [82, 83]. However, the expression of Nox1 in human stomach has been questioned [48], though another Nox isoform could play a similar role in humans.…”
Section: Nox Proteins In Signal Transductionmentioning
confidence: 99%